2007
DOI: 10.1093/tropej/fmm051
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Colonization Among Children up to 6 Years: Results of a Community-based Study from Northeastern Brazil

Abstract: This study shows that children living in low socioeconomic status and poor hygienic conditions are infected very early in childhood. It identifies age and H. pylori positive mother as independent risk factors for infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
1
26
0
4
Order By: Relevance
“…The primary risk factors for acquiring H pylori in Brazil are related to unfavorable living conditions experienced during childhood, including low family income, low education levels of the children's parents, lack of proper household sanitary facilities, household crowding or high density housing or in institutions; improper personal hygiene habits, presence of an infected family member, especially the mother, and deficient basic public health services such as supply of piped drinking water, household garbage collection and sewerage with treatment plants for collected waste (9,36,55,56,79,110) .…”
Section: Group 5 Epidemiology Of Infection and Proposals For Action mentioning
confidence: 99%
“…The primary risk factors for acquiring H pylori in Brazil are related to unfavorable living conditions experienced during childhood, including low family income, low education levels of the children's parents, lack of proper household sanitary facilities, household crowding or high density housing or in institutions; improper personal hygiene habits, presence of an infected family member, especially the mother, and deficient basic public health services such as supply of piped drinking water, household garbage collection and sewerage with treatment plants for collected waste (9,36,55,56,79,110) .…”
Section: Group 5 Epidemiology Of Infection and Proposals For Action mentioning
confidence: 99%
“…Poucos estudos sobre a prevalência do H. pylori foram realizados com uma amostra grande o suficiente e com métodos diagnósticos não invasivos validados localmente em crianças de comunidades indígenas 10,11 . Portanto, é de vital importância que obtenhamos uma melhor compressão da epidemiologia da infecção por H. pylori em crianças das chamadas comunidades primitivas.…”
Section: Introductionunclassified
“…Previous epidemiological studies have shown a high prevalence of H. pylori infection in Brazil (2,20,24). H. pylori infection, generally acquired in childhood, persists asymptomatically for decades in most individuals.…”
mentioning
confidence: 98%